Kandungan Minyak 30 Genotipe Jagung dan Korelasinya terhadap Beberapa Karakter Agronomi - Karomah, Nailatul; Suwarno, Willy Bayuardi; Azrai, dan Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Industrial demand for maize oil has been increasing and therefore corn breeding efforts began to focus on developing improved maize varieties with high oil content. The objectives of this research were to determine oil content of maize genotypes and its relationship with several agronomic traits. The oil content of maize genotypes ranged from 3.77 to 5.46%. Based on the correlation analysis, oil content correlated significantly with plant height, ear height, embryo weight, kernel weight, endosperm weight, and embryo and endosperm area ratio. In addition, oil content of maize genotypes could be estimated by a regression model involving embryo and endosperm area ratio, endosperm weight, ear height, cob lenght, number of kernel rows, number of kernel per row, cob diameter, and husk coverage (R2 = 79.66%; P = 0.0001). The oil-correlated traits and regression model obtained can be considered for facilitating selection for high oil maize genotypes. In addition, the results indicate that high oil maize can be bred and selected without affecting yield.Keywords: high oil maize, simultaneous selection, stepwise regression